The following question is inspired by this problem.
The diagram depicts a bead sliding on a rough circular wire (due to the influence of gravity) as shown below:
The circular arc is of unit radius centred at the origin. The bead is of unit mass and slides down the surface starting from the point ( − 1 , 0 ) . Initially, the downward speed of the bead is 0 . 5 m / s . The coefficient of friction of the wire is μ = 0 . 5 .
The goal of this question is to find the value of A at time t = 0 . 5 s where:
A = d θ d θ ˙
Enter your answer as ⌊ ∣ 1 0 0 0 A ∣ ⌋
Take g = 1 0 m / s 2
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This was a fun problem. Here are my two cents. Let ( x , v , a ) be the tangential position, velocity, and acceleration, respectively.
A = d θ d θ ˙ = d θ / d t d θ ˙ / d t = θ ˙ θ ¨ = v a
The rest is just number crunching. Code below:
1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 |
|
I will lay out a few brief steps for the approach to this question. I encourage the solvers to post more detailed solutions.
Using the laws of motion, the equation of motion is: θ ¨ = 1 0 cos ( θ ) − 5 sin ( θ ) − 2 θ ˙ 2
Now comes the important step: d t 2 d 2 θ = d t d θ ˙ = d θ d θ ˙ d t d θ = d θ d θ ˙ θ ˙
Replacing this in the EOM, we get: d θ d θ ˙ θ ˙ = 1 0 cos ( θ ) − 5 sin ( θ ) − 2 θ ˙ 2
This differential equation can be solved to obtain a closed form solution where θ ˙ is a function of θ . Solving for θ as a function of time would require numerical approaches. Recall that the initial conditions are:
θ ˙ ( 0 ) = 0 . 5 and θ ( 0 ) = 0
Looking forward to seeing more elaborate solutions which demonstrate how to obtain the equation of motion and its solution.
Problem Loading...
Note Loading...
Set Loading...
The differential equation of the particle is m ( − cos θ sin θ ) θ ¨ + m ( sin θ cos θ ) θ ˙ 2 = N ( sin θ cos θ ) + μ N ( cos θ − sin θ ) + m g ( − 1 0 ) where N is the magnitude of the normal reaction. Thus m θ ¨ = − μ N + m g cos θ m θ ˙ 2 = N − m g sin θ and hence, eliminating N , θ ¨ + μ θ ˙ 2 d θ d [ 2 1 θ ˙ 2 e 2 μ θ ] 2 1 θ ˙ 2 e 2 μ θ θ ˙ 2 = g ( cos θ − μ sin θ ) = g ( cos θ − μ sin θ ) e 2 μ θ = 4 μ 2 + 1 g [ 3 μ e 2 μ θ cos θ + ( 1 − 2 μ 2 ) e 2 μ θ sin θ − 3 μ ] + 8 1 = 4 μ 2 + 1 2 g [ 3 μ cos θ + ( 1 − 2 μ 2 ) sin θ − 3 μ e − 2 μ θ ] + 4 1 e − 2 μ θ ( ⋆ ) With g = 1 0 and μ = 2 1 we want to find the value of θ attained at time t = 2 1 . Thus we need to solve the equation 2 1 = ∫ 0 θ 6 0 cos u + 2 0 sin u − 5 9 e − u 2 d u and this can be done numerically, obtaining θ = θ 0 = 1 . 0 5 3 7 6 5 4 . We can now calculate θ ˙ ( θ 0 ) and θ ¨ ( θ 0 ) , using ( ⋆ ) and the fact that θ ¨ = 1 0 cos θ − 5 sin θ − 2 1 θ ˙ 2 , obtaining A = θ ˙ ( θ 0 ) θ ¨ ( θ 0 ) = − 1 . 0 5 4 4 7 making the required answer equal to 1 0 5 4 .